OPTIMIZING CHARACTER EDUCATION AND RELIGIOUS EDUCATION IN DOLLY LOCALIZATION AREA - Kirana, Galuh Eka Candra; Hafidz, Hafidz (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
This study aims to determine the application of religion and the development of children's character in the localization of Dolly Alley. Then to find out the learning process that is suitable for children in the location and find out how parents model good character and religious education in the location. The method used is qualitative with a case study approach. The main techniques for collecting data are observation and in-depth interviews. The respondent of this research is the Religious Teacher at SDN Putat Jaya 1. The closure of the area had an impact on the local community who lost their jobs. Including children who are affected, for example, children dropping out of school because their parents do not have jobs, even though the local government helps with MSME businesses but does not last long. This phenomenon results in children dropping out of school and low motivation to learn and eventually becoming undirected. These children have deviant behavior and bad character. Therefore, the author raised this title, able to provide solutions to the problems of character education and religious education for children in Gang Dolly by reducing school dropout rates and increasing learning motivation.